2022
DOI: 10.3390/cells11040590
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Epithelial AMPK Deficiency Causes Delayed Colonic Epithelial Repair in DSS-Induced Colitis

Abstract: Dysfunctions in the intestinal barrier, associated with an altered paracellular pathway, are commonly observed in inflammatory bowel disease (IBD). The AMP-activated protein kinase (AMPK), principally known as a cellular energy sensor, has also been shown to play a key role in the stabilization and assembly of tight junctions. Here, we aimed to investigate the contribution of intestinal epithelial AMPK to the initiation, progression and resolution of acute colitis. We also tested the hypothesis that protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Likewise, AMPK-P is elevated in response to energy depletion, and, as such, should be appropriately elevated to support energetically taxing wound healing [ 34 , 35 ]. Taken with a recent study, which used a transgenic AMPK KO mouse model to show delayed epithelial repair during DSS colitis and attributed the changes to decreased IEC proliferation, epithelial barrier maturation, and differentiation during the recovery phase of DSS colitis, these data further support our observations [ 36 ]. Indeed, through comparison of immunofluorescence at peak colitis and during recovery, it was observed that the control group showed slightly increased AMPK-P:DAPI and Ki67:DAPI at peak disease but displayed an increase in expression during recovery, while colon tissue in mice receiving allopurinol showed no initiation of these wound healing responses ( Figure 4 C,D).…”
Section: Resultssupporting
confidence: 90%
“…Likewise, AMPK-P is elevated in response to energy depletion, and, as such, should be appropriately elevated to support energetically taxing wound healing [ 34 , 35 ]. Taken with a recent study, which used a transgenic AMPK KO mouse model to show delayed epithelial repair during DSS colitis and attributed the changes to decreased IEC proliferation, epithelial barrier maturation, and differentiation during the recovery phase of DSS colitis, these data further support our observations [ 36 ]. Indeed, through comparison of immunofluorescence at peak colitis and during recovery, it was observed that the control group showed slightly increased AMPK-P:DAPI and Ki67:DAPI at peak disease but displayed an increase in expression during recovery, while colon tissue in mice receiving allopurinol showed no initiation of these wound healing responses ( Figure 4 C,D).…”
Section: Resultssupporting
confidence: 90%
“…Olivier et al. also reported that the loss of AMPK in Caco‐2 monolayers leads to a delay in tight junction reorganization and repositioning during calcium conversion, resulting in impaired paracellular permeability [32] . The activation of AMPK with AMPK activator 991 accelerated the reassembly and reorganization of tight junction in Caco‐2 monolayers after calcium conversion and improved paracellular permeability [33] .…”
Section: Resultsmentioning
confidence: 98%
“…[31] Olivier et al also reported that the loss of AMPK in Caco-2 monolayers leads to a delay in tight junction reorganization and repositioning during calcium conversion, resulting in impaired paracellular permeability. [32] The activation of AMPK with AMPK activator 991 accelerated the reassembly and reorganization of tight junction in Caco-2 monolayers after calcium conversion and improved paracellular permeability. [33] In this study, we demonstrated that Picroside III treatment significantly mitigated the inactivation of AMPK in TNF-α-induced Caco-2 cells, and that the silence of AMPK with siRNA could significantly attenuate the upregulation of Picroside III in ZO-1 and occludin expressions and the downregulation of claudin-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus salivarius can inhibit the adhesion of ETEC K88 to IPEC-J2 cells and, at the same time, has the ability to reduce the pro-inflammatory cytokines IL-1β, TNF-α, IL-8 and TLR4 and significantly reduce the phosphorylation of p38 MAPK and p65 NF-κB, which indicates that Lactobacillus salivarius may reduce inflammation-related cytokines by inhibiting the phosphorylation of p38 MAPK and blocking the NF-κB signaling pathway [ 35 ]. IL-6 has been reported to play a key role in the amplification of inflammatory signals in the gut, and it can inhibit the NF-κB pathway and pro-inflammatory cytokine IL-6 production to reduce intestinal inflammation [ 36 ]. This is consistent with the test results showing that the protein expression of TLR4, NF-κB and MyD88 and the mRNA expression of TNF-α , IL-1β and IL-6 in the L.S + E. coli group were lower than those of the E. coli group ( p < 0.01).…”
Section: Discussionmentioning
confidence: 99%